INFORMĀCIJAS TEHNOLOĢIJU IZMANTOŠANA BĒRNA PSIHOFIZIOLOĢISKĀ STĀVOKĻA NOVĒRTĒŠANĀ UN UZVEDĪBAS KOREKCIJĀ (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The paper deals with the information technology methods of earley diagnostics and correction of nervous system disorders. The effective method which allows to improve the psychoemotional sphere of people with different functional disorders of nervous system and to make correction work with them is functional bioregulation with biofeedback. 24 hyperactive children were observed in current investigation. The assessment of psychophysiological state of children was carried out. The analysis of behaviour of children was organised as a computer game. Electroencephalograms of children were registered and their individual peculiarities were estimated. The behaviour correction of hyperactive children with attention deficiency by the method of functional bioregulation with biofeedback was carried out. The results of investigation showed that functional bioregulation training procedures normalise the bioelectrical activity of hyperactive children brain, decrease behaviour impulsiveness, improve abilities to concentrate attention and make better work capabilities.